HUBUNGAN BERAT BADAN, ASI EKSKLUSIF, MP-ASI DAN ASUPAN ENERGI DENGAN STUNTING PADA BALITA USIA 24–59 BULAN DI PUSKESMAS LUBUK BUAYA - Maria Nova; Olivia Afriyanti (JURNAL KESEHATAN PERINTIS, 2018)
The incidence of stunting in infants is one of the global nutritional problems. When compared with the limit of "non public health problems" WHO recruited for the problem of stunting by 20%, then almost all countries in the world experience public health problems. This study aims to determine the relationship between birth weight, exclusive breastfeeding, giving complementary feeding and energy intake with the incidence of stunting in infants aged 24-59 months in the working area of ​​the Lubuk Buaya Health Center in Padang City. The design in this study was Cross Sectional (cross-sectional data. Birth weight data, Giving Exclusive ASI and Giving MP-ASI was obtained through interviews using a questionnaire. Energy Intake data was obtained through interviews using Quantitative Food Frequency (FFQ). with a total sample of 94 toddlers aged 24 - 59 months, the following results were obtained according to Lameshow (1997): in the group of toddlers aged 24 - 59 months who experienced stunting 60% of them had low birth weight as much as 17.4% of toddlers stunting no exclusive breastfeeding, 34.6% lack of complementary breastfeeding and 36.8% lack of energy intake in the stunting under-five group, stunting in 24 - 59 months of age with birth weight had a significant relationship ( p = 0.002) The provision of exclusive breastfeeding with the incidence of stunting in infants has a non-significant relationship (p = 0.327). MP-ASI supplementation with the incidence of stunting in infants aged 24 - 59 months had a significant relationship (p = 0.001). Energy intake with the incidence of stunting in infants has a significant relationship (p = 0.005). The conclusion of birth weight, complementary feeding, and energy intake had a significant relationship with the incidence of stunting in infants aged 24 - 59 months and exclusive breastfeeding did not have an insignificant relationship with the incidence of stunting in infants aged 24 - 59 months.